Sustained Autonomy - An alternative political status for small islands? - Quentin-Baxter, Alison (Victoria University of Wellington Law Review, 1994)
This article originated as a paper presented at the Pacific Regional Seminar, Port Moresby, Papua New Guinea, 8-10 June 1993, of the Special Committee on the Situation with regard to the Implementation of the Declaration on the Granting of Independence to Colonial Countries and Peoples. Alison Quentin-Baxter first discusses what she sees as the problems with both free association and integration of small island communities. She then advances an alternative model which she labels "sustained autonomy".